The impact of the repercussions of the Coronavirus (COVID-19) pandemic on the rural agricultural sector from farmer’s point of view in Egypt - El-Ghazaly, Mamdouh Mohsen; Zayed, Mohamed AlSayed Ahmed; Asy, Shereen Mohammed Mahmoud (Journal of agricultural, environmental and veterinary sciences, 2023)
This study mainly aimed to study the impact of the Coronavirus (COVID-19) pandemic on the rural agricultural sector from the point of view of the respondent’s farmers in Egypt. The means of achieving this goal have been limited to the following sub-objectives: Identify some of the distinctive personal characteristics of the respondent’s farmers. Determine the levels of appreciation of respondents farmers for the impact of the repercussions of the Corona pandemic on the rural agricultural sector, including (the agricultural production dimension, the extension communication dimension, and the economic marketing dimension). Identify the proposals of the respondents farmers to reduce the effects of the Coronavirus pandemic on the rural agricultural sector in Egypt to lay the scientific and practical foundations in dealing with the crises that the rural agricultural sector may be exposed to in the future. The study population is 4,540 farmers in all eight studied villages, namely the villages of Al-Abadi, Nadiba Damanhour district, Kom Zamran, Al-Masin Dalingat district Beheira governorate, the villages of Samalut, Maghagha Malwa district, Bani Obaid and Abioha, Abu Qurqas district Minya governorate. A random sample was selected from them representing 5% of farmer’s population, amounted to 130 respondents from Beheira Governorate and 97 from Minya Governorate. Where the total of respondents are 227. It was found that 51.98%, 34.36%, 13.66% of the respondents estimated the negative effects of the Coronavirus on the rural agricultural sector were high, medium and low respectively.